Early Marriage and Its Effect on Maternal Health in the Danuwar Community - Thapa, Rekha (DEPAN, 2025)
Background: This study examines how early marriage affects the health of Danuwar women in Melamchi Municipality, Nepal, where it is still a major social problem with wide-ranging socioeconomic and health effects. The study intends to evaluate the maternal health issues associated with early marriage, determine the major factors influencing early marriage, and examine the sociodemographic traits of women who got married young. Methods: A cross-sectional study design was used, and 51 respondents were chosen by systematic random sampling from 102 early-married women identified using city records. A structured questionnaire was utilized for data collection, and descriptive and inferential statistics, such as logistic regression models and chi-square tests, were used for analysis. Results: Results showed 49.01% of respondents were married before the age of 13, and 66.67% of respondents were part of joint families. There were notable maternal health issues, such as anemia (41.2%), miscarriage (14.7%), and delivery problems (32.3%), all of which were substantially linked to early pregnancy (p < 0.05). 69.44% of respondents also said they didn’t know anything about contraception. Early marriage was found to be strongly predicted by cultural customs (p = 0.002) and illiteracy (OR = 3.2, p < 0.001), according to logistic regression analysis. Conclusion: The study emphasizes that to lessen the negative impacts of early marriage, specific community-based interventions are required, such as educational campaigns, legal support, and programs that raise awareness of reproductive health issues.